Proposed market design of retail electricity markets incorporating SPP distribution systems in Thailand - Woravich Rojthavol; Weerakorn Ongsakul; Singh, Jai Govind; Xue, Wenchao; Nopbhorn Leeprechanon; PEA-AIT Education Cooperation Project (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
In the face of such challenges about electricity supply industry (ESI), new market participants are emerging in distribution network and may be reforming ESI structure in developing countries. In case of Thailand, enhanced single buyer model is conventional power system for long period ago. At present, Thailand{u2019}s governments have permitted SPP to construct own distribution grid for servicing their large customers at the uniform tariff which is equal to that of PEA. Then, introducing competitive pressures takes place at the retail market because eligible customers would have options to purchase energy from either public distribution company (PEA) or private supplier of SPP through SPP{u2019}s network. On the other hand, problem of potential cross subsidy is severe topic. When regulated and unregulated activities are provided in term of distribution network with affiliated generators in retail market, the conflict of interest between PEA and SPP is automatically generated because of being competitive players on the retail market. Hence, the aim of the present work is to investigate the suitable market model for fairly retail electricity market based on context in Thailand. Furthermore, we intend to improve the electricity supply industry structure which is moving towards a competitive market and decrease problem issues about occurring irregulated market, own generation by customer, increasing cost subsidy due to decreasing customer, no market trading power and information unavailability. To accomplish this aim, this thesis establishes the developed models by the principle of ESI restructuring introducing to competitive market, and these models classify by three main-structure groups namely, distribution wire open access through third-party access (TPA), combined the multiple networks to the pool system and other model groups. Moreover, this presents the approaches of organizational structure design and commercial design in retail electricity market, and then illustrates alternatives of possible business models based on network constraints in Thailand. Moreover, these models are investigated by considering of various perspective to improve conflict of interest in aspect of structure barriers and regulated retail tariff. Finally, the decision tree approach is performed for decision making to choose the proposed model which is appropriate to apply with retail market limited in industrial zones in Thailand.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy, School of Environment, Resources and Development
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Electric power distribution -- Thailand; Electricity -- Marketing -- Thailand